On the potential of supersonic particle deposition to repair simulated corrosion damage. (March 2015) - Jones, R.; Matthews, N.; Green, R.; Peng, D.
Highlights: Previous studies have been limited to constant amplitude laboratory tests. This paper is the first to study SPD on structures under representative flight load spectra. This study suggests that SPD has the potential to address corrosion damage in operational aircraft. Abstract: Previous constant amplitude laboratory tests have shown that supersonic particle deposition (SPD) can be used, as an alternative to mechanically fastened doublers, to enhance the structural integrity of aircraft structures. This paper compliments these findings via a numerical study into the potential for SPD scarf repairs to repair simulated corrosion in thin aircraft structural components. The results of this study, when taken in concert with the results of prior applications to full scale fatigue tests and laboratory tests, suggest that a SPD scarf repair to simulated corrosion damage subjected to load spectra representative of helicopters, fighter, maritime, and transport aircraft has the potential to give lives that are compare favourably with either the original design objectives or the stated operational life of the aircraft.